Understanding the human genome project - Palladino, Michael Angelo (San Francisco : Benjamin Cummings, 2002)
Contains a brief explanation to the understanding of human genetics including the history, social, and ethical implications of the genome project.
Includes bibliographical references (p. 34-36).
Adult.
Adult
Keywords: Human Genome Project -- Popular works; Human Genome Project; Human Genome Project; Human genome -- Popular works; Medical genetics -- Popular works; Genetics; Medical genetics; Genome, Human -- Popular Works